Pengaruh Literasi Keuangan, Risk Tolerance dan Overconfidence pada Keputusan Investasi Mahasiswa di Masa Pandemi Covid-19: Studi kasus: Mahasiswa Investor KSPM di Galeri Investasi Universitas Pelita Bangsa - Purwanti Purwanti; Elvi Selga Seltiva (STIM LASHARAN JAYA MAKASSAR, 2022)
This study aims to determine the effect of financial literacy, risk tolerance, and overconfidence on student investment decisions during the COVID-19 pandemic. This study uses a case study on student investors of KSPM in the investment gallery. The sampling method in this study uses purposive sampling or the technique of determining the number of samples with certain criteria until the number of samples used in the research is reached. A total of 100 people were sampled. This type of research is a quantitative research using a questionnaire taken from the research instrument using a Likert scale. To test the hypothesis, the researcher used primary data obtained from the answers to a questionnaire of 100 respondents, then the data was processed using the smartPLS 3.3 (Partial Least Square) software.Based on the results of this research, shows that financial literacy has a positive and significant effect on investment decisions with a p-value of 0.000 <0.05. And risk tolerance also has a positive and significant effect on investment decisions with a value of 0.002 < 0.05. However, the results of the test for the effect of overconfidence on investment decisions show a p-value of 0.340 > 0.05, which means that overconfidence has no significant positive effect on investment decisions. This proves that overconfidence is not always a factor influencing investment decisions because the level of confidence of each individual varies depending on the person's state of mind.